CAMEL rating approach to assess the insurance operators financial strength - Yakob, Rubayah; Yusop, Zulkornain; Radam, Alias; Ismail, Noriszura (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study aims at looking at the financial strength based on the CAMEL rating system for each of the conventional life insurers and takaful operators. The existing financial indicators, such as the margin of solvency (MOS), risk-based capital (RBC) and claim paying ability (CPA) rating, present their own constraints in providing information concerning the financial position of the operators to the policyholders and the public. The data used for the twenty life insurance and takaful companies operating during the period of 2003 to 2007 consists of twenty-three financial ratios. The factors (values) generated by factor analysis applied on twenty-three financial ratios reflect the five components in the CAMEL rating system. The results show that the CAMEL rating is a promising approach in providing an overview of the financial strength of the life insurer/takaful operator for the benefit of policyholders and the public.